Documents of the Christian church - Bettenson, Henry, 1908-1979; Maunder, Chris (Oxford University Press, 2011)
This selection of writings from the most important moments in the history of Christianity has become established as a classic reference work, providing insights into 2000 years of Christian theological and political debate.